BIOMASS FORMATION BY DIFFERENT COLLECTIONS OF PLEUROTUS SPP. DURING SUBMERGED GROWTH (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Many species of the genus Pleurotus (Fr.) P. Kumm. (Oyster mushrooms) are known as valuable edible and medicinal fungi, cultivated worldwide. The studied 18 different collections of five Pleurotus species (P. ostreatus, P. cornucopiae, P. eryngii, P. pulmonarius, and P. cystidiosus) during submerged growth in malt extract medium formed round shaped fluffy pellets and disperse mycelium. After seven days of cultivation, they accumulated up to 29.46 g/L biomass, while after 14 days the amount increased up to 40.4 g/L, reaching the value of commercial P. ostreatus 22 strain. More than 30.0 g/L biomass was formed in nine from 12 P. ostreatus collections, among which Armenian (SB24 and SB25), French (Po/28) and Spanish (N001) strains, as ecologically safe resources are perspective for further study to develop mushroom-based biotech products, food, pharmaceuticals and cosmeceticals.
Keywords: biomass; biotech products; edible; medicinal; mycelium; Pleurotus species; submerged growth